Do income differentials influence the flow of migrant workers from the Philippines? - Gonzalez, Eduardo T. (1995)
The emigration of Filipino workers is explained with an "international" variant of Harris-Todaro migration model for developing countries. It is hypothesized that the decision to emigrate is a function of the expected income differential between the origin and destination countries, net of moving costs (intermediation expense, transportation costs). Using a log-linear emigration function and employing data from the 1988 Philippine national demographic survey, regression results suggest that the higher the income differential (and the lower the moving costs), the higher the tendency to emigrate. In order to stem the flow of Filipino technical and professional workers and avoid critical shortages in the supply of skills and services, an appropriate policy choice is to provide subsidy-financed incentives that would require "keying" wages to concrete performance standards at the firm level. That should spur a "newly-industrializing" type of growth-which is the key to minimizing serious imbalances in economic opportunities between the Philippines and other countries.
Keywords: Emigration and immigration -- Economic aspects; Foreign workers, Filipino; Wage differentials